Surveillance and Monitoring Brucellosis at Denpasar Veterinary Center Working Area in the 2016 - Suharsono H (Journal of Global Pharma Technology, 2016)
Background: The situation of Brucellosis in the working area of the Denpasar Veterinary Center (BBVet) varies between provinces. The provinces of Bali and NTB have been declared free of Brucellosis. However, specifically in NTT, only Sumba Island was declared free of Brucellosis. The situation of Brucellosis in NTT Province, on the island of Timor, Belu Regency and TTU is a heavily infected area of brucellosis with a prevalence of > 2%, while other islands have an unknown prevalence. One Brucellosis reactor found in Ende District in 2006. Continuous surveillance was carried out as an early detection step to keep the area free. Objectives: Brucellosis and monitor the possibility of entry/emergence of new reactors in the region, and to determine the prevalence of Brucellosis in areas that are not yet free of Brucellosis. Methodology: The samples tested were samples received by the BBVet Denpasar Bacteriology laboratory during 2016. The samples were tested using the Rose Bengal Plate Test (RBPT) method if positive continued with the Complement Fixation Test (CFT) test. Results: A positive sample of CFT expressed as a Brucellosis reactor. The test results of 4,602 serum samples from Bali Province and 2,504 serum samples from NTB Province were all negative for Brucella antibodies. Whereas serum samples from NTT Province were 1,533 samples, three positive samples were CUC brucellosis; namely, two (2) positive samples from 175 serum samples came from Malacca District and one (1) positive sample from 73 serum samples came from North Central Timor District ( TTU). Whereas samples from the districts of Alor, Ende, Lembata, Manggarai, West Manggarai, East Manggarai, Nagekeo, Ngada, RotenDao, Southwest Sumba, West Sumba, East Sumba, East Timor Tengah (TTS), and Kupang City, Conclusion: all negative. Based on these data it can be concluded that the Provinces of Bali and NTB are still free of Brucellosis.Keywords: Brucellosis, BPT, CFT, Bali, NTB. NTT.